Am I seeing myself, my friend or a stranger? The role of personal familiarity in visual distinction of body identities in the human brain. (October 2016) - Kruse, Barbara; Bogler, Carsten; Haynes, John-Dylan; Schütz-Bosbach, Simone
Abstract: Several brain regions appear to play a role in representing different body identities. The specific contribution of each of these regions is still unclear, however. Here we investigated which brain areas enable the visual distinction between self and other bodies of different familiarity, and between familiar and unfamiliar other individuals, and moreover, where identity-specific information on the three individuals was encoded. Participants were confronted with standardized headless human body stimuli either showing the participant's own, a personally familiar or an unfamiliar other body, while performing a luminance discrimination task. Employing multivariate pattern analysis, we were able to identify areas that allowed for the distinction of self from personal familiar other bodies within the medial prefrontal cortex (mPFC) and posterior cingulate cortex/precuneus. Successful distinction of self from unfamiliar others was possible in the left middle frontal gyrus, the right inferior frontal gyrus, the left pre-supplementary motor area and the right putamen. Personally familiar others could be distinguished from unfamiliar others in the right temporoparietal junction (TPJ). An analysis of identity-specific information revealed a spatial gradient ranging from inferior posterior to superior anterior portions of the mPFC that was associated with encoding identity-related information for self via familiar to unfamiliar other bodies, respectively. Furthermore, several midline and frontal regions encoded information on more than one identity. The TPJ's role in deviance detection was underlined, as only identity-specific information on unfamiliar others was encoded here. Together, our findings suggest substantial spatial overlap in neural correlates of self and other body representation and thus, support the hypothesis of a socially-related representation of the self.